2002
DOI: 10.1002/1521-3757(20020902)114:17<3406::aid-ange3406>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

An Alkynylboronic Ester Annulation: Development of Synthetic Methods for Application to Diversity-Oriented Organic Synthesis

Abstract: Diversity-oriented synthesis aims to prepare complex and diverse small molecules efficiently. These molecules can be used to explore biology-our goal is to be able to do so in a systematic way. [1] Whereas complex molecules can be synthe-sized efficiently using coupled complexity-generating reactions, [2] the goal of developing diversity-generating pathways yielding products with a high degree of skeletal diversity has not yet been realized. The development of synthetic pathways incorporating branch points hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…In 2002, Schreiber and Micalizo showed that allyldialkoxyboranates 147 react with allyl alcohols 148 and propargyl alcohols 150 giving allyloxy‐ or propargyloxyalkoxyallylboranes respectively, which were later used in ring closing metathesis reaction to form cyclic boric acid ester compound 149 and 151 (Scheme ). These products are often used for the synthesis of enones . Analogous cyclic products can be obtained in similar reactions of alcohols with alkynyldialkoxyboranes …”
Section: Preparation Of Boron‐substituted 13‐dienesmentioning
confidence: 99%
“…In 2002, Schreiber and Micalizo showed that allyldialkoxyboranates 147 react with allyl alcohols 148 and propargyl alcohols 150 giving allyloxy‐ or propargyloxyalkoxyallylboranes respectively, which were later used in ring closing metathesis reaction to form cyclic boric acid ester compound 149 and 151 (Scheme ). These products are often used for the synthesis of enones . Analogous cyclic products can be obtained in similar reactions of alcohols with alkynyldialkoxyboranes …”
Section: Preparation Of Boron‐substituted 13‐dienesmentioning
confidence: 99%
“…More recently, researchers have introduced libraries based on “folding pathways”, in which library intermediates undergo diverse rearrangements, and “differentiation pathways”, in which intermediates are treated with different reagents to yield different scaffolds 3. Incorporating such branching reaction pathways into library syntheses is a promising strategy for the creation of small‐molecule diversity beyond what can be accessed by using nonbranched synthetic routes 6…”
Section: Methodsmentioning
confidence: 99%
“…These reagent‐based skeletal diversity‐generating transformations are, therefore, also referred to as differentiating processes. For example, the unsaturated, cyclic dialkenylboronic ester 41 has potential for diverse reactivity, and thus, different reagents can be used to transform this common, pluripotent substrate into different products (Scheme ; two are shown), each having a distinct molecular skeleton 31. Treatment of 41 with hydrogen peroxide and sodium hydroxide effects an oxidation which leads to enone 42 .…”
Section: Diversity‐generating Processes and Their Use In Dos To Gementioning
confidence: 99%